A systematic literature review on the success factor of innovation commercialization performance - Abdul Hamid, Norhadilah (2014)
This paper explores and describes some of the directions within the field of innovation commercialization collaboration. The directions are derived from the results of examining 182 research articles that had been published from year 2007 to year 2013 from various established databases. From the systematic literature review process, six main factors have been identified as success factors of innovation commercialization. The factors are organizational resources, knowledge management, strategic orientation, organizational support, contextual factor and lastly collaboration.